2001
DOI: 10.1359/jbmr.2001.16.6.1056
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Periprosthetic BMD After Uncemented Total Hip Arthroplasty with Dual-Energy X-Ray Absorptiometry—a 3-Year Follow-Up Study

Abstract: Insertion of a metallic implant into the femur changes bone loading conditions and results in remodeling of femoral bone. To quantify changes in bone mass after uncemented total hip arthroplasty (THA), we monitored femoral bone with dual-energy X-ray absorptiometry (DXA). The periprosthetic bone mineral density (BMD) was measured with Lunar DPX densitometry in seven Gruen zones and the total periprosthetic area at scheduled time intervals in 22 patients during a 3-year follow-up. BMD decreased significantly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
126
3
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 20 publications
13
126
3
3
Order By: Relevance
“…Kilgus et al (1993) noted largest BMD loss (35%) in the most proximal 1 cm of the medial femoral cortex. Longitudinal studies have also been performed (Trevisan et al 1997, Venesmaa et al 2001, confirming the results of cross-sectional studies.…”
Section: Discussionsupporting
confidence: 70%
“…Kilgus et al (1993) noted largest BMD loss (35%) in the most proximal 1 cm of the medial femoral cortex. Longitudinal studies have also been performed (Trevisan et al 1997, Venesmaa et al 2001, confirming the results of cross-sectional studies.…”
Section: Discussionsupporting
confidence: 70%
“…Augmented bone ongrowth has been documented as early as 3 weeks and as persisting for some years [2-4, 11, 26, 27]. However, as much as 20% to 30% of bone loss at the proximal femur has been reported after THA for the same period as a consequence of proximal stress shielding [8,21,30]. It also is expected and observed that the HA coating resorbs with time [1-3, 18, 19, 27, 28], although it is unknown whether this adversely influences the amount of long-term bone ongrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Based on short-term bone density studies using dualenergy xray absorptiometry, gender and bone stock are believed to influence ongrowth and resorption [20,30]. Although age certainly is related to bone stock quality, a direct correlation between age and bone ongrowth onto implants such as uncemented HA-coated hip stems has not yet been proven.…”
Section: Introductionmentioning
confidence: 99%
“…Regional bone loss has been studied widely using dual energy X-ray absorptiometry (DXA) [16,18], occurs around both the femoral and pelvic implant components [24], and is most rapid within the first six months after surgery [ 15,17,23,34]. Subjects with low pre-operative BMD show the greatest bone loss after THA [32], however it is unknown whether this results in a higher rate of aseptic loosening.…”
Section: Introductionmentioning
confidence: 99%